Surface‐Enhanced Mid‐IR Gas Sensor Employing Wavelength‐Tunable Bloch Surface Waves. Issue 10 (21st August 2022) - Nong, Jinpeng; Zhao, Bo; Xiao, Xin; Min, Changjun; Yuan, Xiaocong; Somekh, Michael; Feng, Fu
Abstract: In this paper, a wavelength‐tunable Bloch surface waves (BSWs) platform for the illustration of SO2 sensing in mid‐IR region, which is consisted of a 1D photonic crystal with an omnidirectional bandgap and an attached layer of phase change material (Ge2 Sb2 Te5, GST) is theoretically designed. Based on such configuration, the spectral response of the sensor can be actively modulated by adjusting the crystallization fraction of GST and the incident angle of light, with ultrahigh quality‐factor at the order of 10 4 within a wide waveband. Such specific designed BSWs‐assisted IR gas sensor significantly enhances the molecular absorption signal by 10 6 ‐fold. This allows not only to qualitatively identify the species of the probed gas molecules but also quantitatively measure the concentration of the SO2 molecules, showing unique advantages over the conventional BSWs‐based refractive index sensors working in visible and near‐IR region. It is further demonstrated that the sensor can be used for early warning of SO2 concentration, of which the threshold value is determined by the incident angle and the refractive index of the prism. This work provides an alternative and effective strategy for high‐performance gas sensing in the mid‐IR. Abstract : A wavelength‐tunable Bloch surface waves platform is designed for the illustration of SO2 sensing in mid‐IR region. It can not only qualitatively identify the species of the gas molecules but also quantitatively measure its concentration. It can be used for early warning of SO2 concentration, of which the threshold value is determined by the incident angle and prism refractive index.